Possible Role of High-Molecular-Weight Salivary Proteins in Astringency Development - Elvira Manjón; Ignacio García-Estévez; María Teresa Escribano-Bailón (Foods, 2024)
Since the initial findings that food tannin/salivary protein interaction and subsequent precipitation is the main cause of the astringency development, numerous studies have concentrated on the supramolecular characterization of these bindings. Most of these works have focused on the low-molecular-weight salivary proteins, in particular proline-rich proteins, hardly considering the involvement of the high-molecular-weight salivary proteins (HMWSPs). Herein, different techniques such as fluorescence quenching, Isothermal Titration Calorimetry and HPLC-MS-DAD were employed to determine the occurrence of molecular interactions between three HMWSPs, namely, mucin, α-amylase and albumin, and a complex extract of tannins composed mainly of flavan-3-ols. The obtained results prove the capability of the three HMWSPs to effectively interact with the flavan-3-ol extract, involving different forces and action mechanisms. Flavan-3-ols are capable of interacting with mucins by a mechanism that includes the formation of stable ground-state complexes that led to approximately 90% flavan-3-ol precipitation, while for albumin and α-amylase, the interaction model of a “sphere of action” was established, which represented only 20% flavan-3-ol precipitation. These data highlight the relevance of including HMWSPs in astringency analyses, paying special heed to the role of mucins in the interaction and subsequent precipitation of dietary tannins.